The Effectiveness of Videos and Animations in Learning Physics in Junior High School Heat Materials - Zakirman Zakirman; Wienda Gusta; Chichi Rahayu (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
At the junior high school level, it is expected that learning Physics will provide students with knowledge and skills so that they can develop competency and hone science skills. Heat material is one of the junior high school physics materials which is dominated by concepts and principles so that it is considered difficult by students. The use of effective media can be one of the solution, namely the use of videos and animations in learning Physics. The type of this research is Research and Development which aims to develop videos and animations in learning physics of heat material. The effectiveness in using of videos and animations was carried out in a limited field test, namely in class VII3 SMP N 1 Pariaman even semester 2019/2020 using before and after experiments. The data collection instrument for the effectiveness test was in the form of tests of students' cognitive learning outcomes before and after using videos and animations. Furthermore, the data were analyzed using a correlated t-test. Based on the results of the analysis, the value of tcount = 6.91 and ttable = 2.04 (tcount > ttable). This shows that there is a significant difference between learning outcomes before using videos and animations in learning Physics and learning outcomes after using videos and animations in learning Physics. Thus, it can be said that videos and animations in physics learning are effective heat materials used in physics learning in class VII SMP Negeri 1 Pariaman.